Psychological correction program of socialization of self-destructive adolescent with communication’s problems - A. Ipatov (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The goal is to show that the causes of self-destructive manifestations in communication in adolescents are not insurmountable obstacles in their socialization. Methodology: with the aim of creating a program of psychological adjustment of adolescents with self-destructive behavior was delivered ascertaining and forming experiment using valid and reliable methods of observation, interviews, psycho-diagnostics. Significance: in modern society the number of self-destructive teenager is great, they need help.